2017
DOI: 10.1111/btp.12518
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting species responses to continued nitrogen and phosphorus addition in tropical montane forest tree seedlings

Abstract: Global changes in nutrient deposition rates are likely to have profound effects on plant communities, particularly in the nutrient‐limited systems of the tropics. We studied the effects of increased nutrient availability on the seedlings of six tree species in montane forests of southern Ecuador in situ. After five years of continued N, P, or N+P addition, naturally grown seedlings of each of the two most common species at each elevation (1000, 2000, and 3000 m asl) were harvested for analyses of leaf morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 85 publications
3
16
2
Order By: Relevance
“…Leaf N/P ratios above 16 for most tree species regardless of elevation indicate the limiting role of P for tree growth in the study area 39 . N and P fertilization experiments at the study sites 40 , 41 , the observed large increase in tree root/shoot ratio along the slope 42 , and in situ measurements of nitrogen mineralization rate and P availability in the soil 43 support this assumption. One plausible explanation is that the temperature decrease is hampering soil biological activity, thereby reducing organic matter decomposition and mineralisation rate.…”
Section: Discussionmentioning
confidence: 67%
“…Leaf N/P ratios above 16 for most tree species regardless of elevation indicate the limiting role of P for tree growth in the study area 39 . N and P fertilization experiments at the study sites 40 , 41 , the observed large increase in tree root/shoot ratio along the slope 42 , and in situ measurements of nitrogen mineralization rate and P availability in the soil 43 support this assumption. One plausible explanation is that the temperature decrease is hampering soil biological activity, thereby reducing organic matter decomposition and mineralisation rate.…”
Section: Discussionmentioning
confidence: 67%
“…Even though several microclimatic, edaphic and hydrologic factors are known to vary along topographical gradients (Takyu et al ., 2003), our PCA of soil variables suggested that variation in the availability of all five plant macronutrients (N, P, Ca, K, Mg) is a major factor differentiating between lower slope and upper slope positions. The results of a fertilisation experiment in the montane forests of the study region revealed a general co‐limitation of tree growth by nitrogen and phosphorus (Homeier et al ., 2012; Cárate‐Tandalla et al ., 2018). Furthermore, nitrogen availability has been shown to decrease greatly towards the upper slope (Wolf et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…N and P availability tends to increase in the pre-montane forest relative to the lower and upper montane forests (Wolf et al, 2011;Werner & Homeier, 2015). Despite of this, tree growth at all sites is predominantly limited by P availability (Graefe et al, 2010;C arate-Tandalla et al, 2018).…”
Section: Study Sitementioning
confidence: 99%